Faktor Faktor Yang Mempengaruhi Pendapatan Petani Minyak Serai Di Kecamatan Pintu Rime Gayo Kabupaten Bener Meriah - Nurlela Nurlela; Jummaini Jummaini; Rasyimah Rasyimah; Ulfa Dilla Amalia (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
The purpose of this study was to determine the factors that influence the income of lemongrass oil farmers in Pintu Rime Gayo District, Bener Meriah Regency. This type of research is descriptive quantitative with the population in this study are the farmers of lemongrass oil business in Pintu Rime Gayo District, Bener Meriah Regency, totaling 71 samples. Methods of data analysis in this study using multiple linear regression and data analysis. The results of data analysis in this study indicate that the price variable partially affects income, while the variables of working capital, labor and land area partially have a positive effect on the income of lemongrass oil farmers in Pintu Rime Gayo District, Bener Meriah Regency.